Puasa dan Relevansinya dengan Ketaqwaan Studi Penafsiran Buya Hamka di dalam Tafsir Al-Azhar - Yani, Yani (Lembaga Yasin AlSys, 2023)
This research is entitled Fasting and Its Relevance to Faithfulness (Study of Buya Hamka Interpretation in Al-Azhar Tafsir). This research is included in the category of library research (library research) with a qualitative approach. So that it can reveal the interpretation of the traditions that exist in society. The purpose of this study is to find out the meaning of fasting, to find out the factors and the role of taqwa, to find out Buya Hamka's interpretation of the verses of fasting and its relevance to piety. The results of this study are people who fast will get results in the form of taqwa provided that they live it with several aspects towards taqwa.